2017
DOI: 10.1111/cei.12992
|View full text |Cite
|
Sign up to set email alerts
|

Specific activation of CD4–CD8– double-negative T cells byTrypanosoma cruzi-derived glycolipids induces a proinflammatory profile associated with cardiomyopathy in Chagas patients

Abstract: Cardiomyopathy is the most severe outcome of Chagas disease, causing more than 12 000 deaths/year. Immune cells participate in cardiomyopathy development either by direct tissue destruction, or by driving inflammation. We have shown that CD4 CD8 [double-negative (DN)] T cells are major sources of inflammatory and anti-inflammatory cytokines, associated with the cardiac (CARD) and indeterminate (IND) forms of Chagas disease, respectively. Here, we sought to identify Trypanosoma cruzi-derived components that lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 55 publications
0
20
0
Order By: Relevance
“…For T. cruzi , these parasites possess membrane lipids that may be involved in the induction of severe disease. It was demonstrated that T. cruzi glycolipids activate a specific γδ-T cell population associated with cardiomyopathy, a severe outcome of Chagas disease ( Passos et al, 2017 ).…”
Section: Immune Evasion and Disease Severitymentioning
confidence: 99%
“…For T. cruzi , these parasites possess membrane lipids that may be involved in the induction of severe disease. It was demonstrated that T. cruzi glycolipids activate a specific γδ-T cell population associated with cardiomyopathy, a severe outcome of Chagas disease ( Passos et al, 2017 ).…”
Section: Immune Evasion and Disease Severitymentioning
confidence: 99%
“…In addition, it is known that the vast majority of the peripheral TCR gamma-delta + cells are DN. Previous studies by us have shown that these cells are associated with Chagas heart disease and that they are specifically activated by glycoconjugates (GCL fraction) from T. cruzi trypomastigotes (24). Thus, the fact that PRO did not increase the expression of CD69 by DN TCR gamma-delta T cells was not surprising.…”
Section: Discussionmentioning
confidence: 99%
“…Antigenic fractions of T. cruzi were obtained using the methodology proposed by Gazos-Lopes et al (23) with adaptations (24). Frozen pellets obtained as described above were suspended in 1.6 mL of ultrapure water (W) and transferred to 13 × 100 mm polytetrafluoroethylene (PTFE)-lined screw cap Pyrex culture tubes.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the prevalence of IFN‐γ‐producing γδ DN T cells over the regulatory response is linked to severe cardiac clinical form of Chagas´ disease. Corroborating, stimulation with T. cruzi ‐derived glycolipids induces TNF‐α and IL‐10 expression by peripheral γδ T cells from indeterminate individuals, while promotes IFN‐γ expression by γδ T cells from cardiac patients 35 . Similar profile was observed in patients with cutaneous leishmaniasis, who present reduced levels of circulating IL‐10‐expressing γδ DN T cells with regulatory properties, while the frequency of αβ DN T cells with proinflammatory properties is increased, when compared to healthy individuals 36 …”
Section: Discussionmentioning
confidence: 99%